Literatur Review Analisis Dampak Kebijakan E-Catalogue terhadap Pengadaan Obat di Era JKN (Jaminan Kesehatan Nasional) - Puspitasari, Mitha (Universitas Islam Indonesia, 2025)
Background: The influence of the e-catalog policy on medication procurement during the National Health Insurance (JKN) era encompasses critical elements such as the necessity to enhance efficiency, accountability, and transparency within the system. All medical facilities working with BPJS Kesehatan are expected to use the e-purchasing application to purchase drugs in this JKN era.Objective: The focus of this literature review was to present empirical evidence about the influence of the e-catalog strategy on the procurement of pharmaceuticals by healthcare institutions during the JKN era.Method: This literature review involved searching for several papers published online via PubMed and Google Scholar using keywords and MeSH terms. The search terms included BPJS e-purchasing, JKN e-purchasing, referral e-purchasing, JKN e-catalog, BPJS, and insurance e-catalog.Result: The e-catalog policy seeks to establish a more equal, efficient, and responsible pharmaceutical procurement system. This aligns with JKN's objective of maximizing resource utilization to enhance the overall quality of healthcare. The execution of the e-catalog policy is an essential measure in modernizing and enhancing the medication procurement system in the JKN era. Consequently, the e-catalog policy is anticipated to yield substantial enhancements in pharmaceutical management and the execution of the JKN program.Conclusion: The e-catalog technique possesses the capacity to markedly enhance drug procurement in the JKN era by augmenting efficiency, accountability, and transparency. System updates will necessitate concentrated efforts.